The Role of Faith and Piety in Empowering Muslim Minority Communities in Asahan District, Indonesia - Nasution, Mhd. Irfan; Budianti, Yusnaili; Salminawati, Salminawati; Suhardi, Suhardi (Yayasan Sembilan Pemuda Indonesia, 2025)
This study aims to analyze the implementation of the Faith and Piety (IMTAQ) in fostering minority Muslim communities in Asahan Regency, with a focus on program planning, implementation, and evaluation. The approach used is qualitative, with data collection techniques including in-depth interviews, field observations, and documentation studies. Informants include IMTAQ managers, speakers, community members, and community leaders. Data is analyzed inductively to understand the dynamics of development within the context of minority communities. The research findings indicate that IMTAQ planning is strategic and inclusive, involving various stakeholders, including religious leaders and local government officials. The programs designed include spiritual strengthening through Quranic reading activities, regular religious study sessions, and economic empowerment initiatives such as sharia-based entrepreneurship training. Program implementation is structured, sustainable, and supported by active community participation. Evaluations indicate that IMTAQ has had a positive impact on improving the quality of faith, piety, and social and moral awareness of the Muslim minority community in the region. The uniqueness of this research lies in IMTAQ’s holistic approach in integrating spiritual guidance with social and economic aspects within the minority Muslim community. These findings contribute to the development of a contextual and inclusive model of religious guidance and have practical implications for application in areas with similar conditions.